Characterization and identification of lung cancer cells from blood cells with label-free surface-enhanced Raman scattering. (12th March 2019) - Zhang, Yanjiao; Zeng, Qiuyao; Li, Linfang; Qi, Minni; Qi, Qichao; Li, Shaoxin; Xu, Junfa
Abstract: Lung cancer has become one of the types of malignant tumors that seriously threaten human life worldwide. It is of great significance to detect lung cancer cells from peripheral blood. In this paper, silver film surface-enhanced Raman scattering (SERS) is used to study SERS spectra of blood cells, various types of lung cancer cell lines and clinically isolated lung cancer cell samples. The results show that the nucleic acid characteristic peaks at 730 cm −1 and 1330 cm −1 are almost absent in red blood cells, and have a small enhancement in white blood cells. There is different enhancement in lung cancer cells; among them there is great enhancement of nucleic acid characteristic peaks in small cell lung cancer (SCLC) cell lines and their clinical cell samples, and smaller enhancement compared to SCLC in non-small cell lung cancer cell lines, such as squamous cell carcinoma, adenocarcinoma and so on. The SERS spectra of blood cells, SCLC cell lines and their clinical cell samples can be completely distinguished by the intensity ratio of the characteristic peak at 730 cm −1 to the subtracted background peak at 900 cm −1 . This study lays a solid foundation for the identification of circulating tumor cells (CTCs) of SCLC by label-free SERS, and may be applied to the label-free SERS detection of CTCs.